The effect of erbium oxide in physical and structural properties of zinc tellurite glass system - Shahrol, Nazirul Nazrin; Mohamed Kamari, Halimah; Muhammad, Farah Diana; Yip, Jen Sheng; Laoding, Hasnimulyati; Mohd Fudzi, Faznny; M.A., Hazlin; Ismail, Zaitizila (Elsevier, 2018)
In this research, the melt-quenching method was used to synthesize a series of zinc tellurite glass systems doped with erbium oxide with the chemical composition of [(TeO2)0.7 (ZnO)0.3]1−x (Er2O3)x at different molar fraction, x = 0, 0.01, 0.02, 0.03, 0.04 and 0.05. X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, density, molar volume, elastic and optical measurements were used to characterize the prepared glass samples. At room temperature, the result of the XRD, FTIR, density, elastic and optical properties were all recorded. An amorphous nature of glass samples is proven by the XRD spectra. The analysis of FTIR spectra shows the presence of functional vibration of tellurite network. It is observed that the density of the glass system increase with the molar fraction of Er2O3. The value of molar volume is found to be directly proportional to the density. Thus, the increment in the density value causes the increment of the molar volume due to the increase of erbium concentration. This in turn results in the creation of excess free volume due to the difference of atomic radius between erbium and tellurite. On the other hand, ultrasonic velocity was used to determine the elastic moduli of the glass systems. The elastic moduli such as longitudinal modulus, shear modulus, bulk modulus and Young's modulus give a fluctuating trend against the concentration of Er2O3. The increase of the elastic moduli is due to the mix former effect. In contrast, the decrease of the elastic moduli is due to the breakdown of Er2O3 in the zinc tellurite glass system which weakens the glass structure of the ternary tellurite system. The optical properties of the prepared glasses were determined by UV–vis analysis. The optical absorption was recorded at room temperature in the wavelength ranging from 220 nm to 800 nm. The optical absorption spectra reveal that fundamental absorption edge shifts to higher wavelength as the content of erbium oxide increase. The values of direct and indirect band gap have been calculated and are observed to decrease with the increase content of erbium oxide. However, the Urbach energy, refractive index, molar refraction and electronic polarizability are shown to be increased with an addition content of erbium oxides.